Sudden cardiac death after implantation of a cardiac resynchronization therapy pacemaker: a case report illustrating that not always less is more. Issue 2 (1st January 2021) - Vollmann, Dirk; Hansen, Claudius; Hunold, Peter; Lüthje, Lars
Abstract: Background: Cardiac resynchronization therapy (CRT) improves symptoms and survival in selected patients with systolic heart failure and ventricular conduction delay. In subjects without prior life-threatening ventricular arrhythmia, clinicians have to select between implanting a CRT pacemaker (CRT-P) or a more complex device with additional defibrillator capability (CRT-D). This individual decision can be challenging in light of the available evidence and the potential risks and benefits. Case summary: A 76-year-old male with non-ischaemic cardiomyopathy, heart failure New York Heart Association Class III, left bundle branch block (QRS duration 185 ms) and a left ventricular ejection fraction of 30% despite optimal medical therapy was indicated for CRT. In light of the patient characteristics and clinical condition, a CRT-P device was implanted. No complication occurred, and the patient was discharged after an appropriate device function was confirmed. Despite the clinical improvement, he died suddenly without prior symptoms approximately 2 months thereafter. Post-mortem device interrogation provided no evidence for device malfunction and confirmed sudden cardiac death (SCD) due to spontaneous ventricular fibrillation. Discussion: Patients indicated for CRT often have overlapping internal cardioverter defibrillator indication for the primary prevention of SCD. By weighing individual risks and potential benefits, clinicians have to decide whether to implant a CRT-P ( less is more ) or a more complex and costly CRT-D device. Despite careful consideration of patient characteristics and clinical conditions, however, SCD can occur in subjects categorized as low risk and implanted with a CRT-P. More data from randomized clinical trials are needed to better support physicians in the often challenging process of selecting the most appropriate device for CRT.